Signs that markets are coming back - Kensinger, John W. (Research in finance, 2014)
Contributions assess hedge fund success, offer extension of real options to include information items as underlying assets, analysis of whether a firms founders can take artificial dividends without consequence, the uneasiness of real estate, and accountability for attempted artificial earnings management.